Inclusive Mosques and Economic Empowerment: A Study from an Islamic Economics Perspective in Urban Muslim Communities - Fahmi, Rizqi Anfanni (Unisia, 2025)
This study explores the role of inclusive mosques within the framework of Islamic economics, focusing on their contributions to economic empowerment, social welfare, and community cohesion. By leveraging qualitative methods, the research draws on a comprehensive literature review of studies indexed in the Scopus database, utilizing thematic analysis to identify key patterns and trends in the literature. The findings reveal that mosques play a pivotal role in promoting financial inclusion through Islamic financial mechanisms, such as zakat and waqf, which serve to foster economic empowerment, particularly in underserved communities. In addition to their financial contributions, mosques are shown to significantly enhance social welfare by providing essential services, including healthcare, education, and support for vulnerable populations. The study also highlights the critical role of architectural inclusivity, with mosque design ensuring accessibility for all congregants, regardless of their physical abilities. This research underscores that inclusive mosques are not only central to spiritual life but also essential in fostering social cohesion and economic development in diverse communities. The paper concludes by offering recommendations for policymakers and mosque leaders to integrate inclusive financial and social strategies, enhancing the impact of mosques as community hubs.